Gomorrha Reise in das Reich der Camorra - Saviano, Roberto 1979- (Hanser, 2007)
A major bestseller in Italy, this is a heroic young man's impassioned account of the decline of Naples under the rule of the Camorra, an organized crime network with a large international reach and stakes in construction, high fashion, illicit drugs, and toxic-waste disposal. Known by insiders as "the System," the Camorra affects cities and villages along the Neapolitan coast, and is the deciding factor in why Campania, for instance, has the highest murder rate in all of Europe and why cancer levels there have skyrocketed in recent years. Author Saviano, who saw his first murder at age 14, worked under cover to investigate the Camorra's control of Chinese factories contracted to manufacture fashion goods, legally and illegally, for distribution around the world, and relates how the abusive handling of toxic waste is causing devastating pollution not only for Naples but also China and Somalia--Publisher's description.
Keywords: Camorra -- Economic aspects; Camorra -- Italy; Camorra; Schattenwirtschaft; Italien; Neapel; German language edition - Nonfiction